KONSEPSI NEGARA KESATUAN MENURUT UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA 1945 - Pratiwi Nur Hidayah; Tomy Michael (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2020)
In the interperting form of a unitary state in Indonesia there are still many different interpretations so that many people who want to build a khilafah state led by the caliph of all sources from the Qur’an. Even before independence the predecessors had determined the form of the state to be a unitary state. The more conflicts occur, many parties whp want to be right themselves in their own way to form a forbidden organization that wants to return to the prophetic as before, establishing a new kingdom and tne occurrence of blasphemy of religion that led to intolerance between people. In this cas the role of the government is able to create togetherness into one unified without differences. In order to create a unitary state and national unity, the author seeks to explain the meaning of the unitary state and compare the shape of the Indonesian state with the Russian state so as to provide an understanding of the true form of the unitary state.Keywords: unitary state, khilafah